Oral Health Attitudes and Behavior among a Group of Dental Students in Bangalore, India - Neeraja, R; Kayalvizhi, G; Sangeetha, P (European Journal of Dentistry, 2011)
Objectives: To evaluate self-reported oral health attitudes and behavior among a group of dental students in Bangalore, India and to compare the oral health attitudes of students of different years of dental school. Methods: A self-administered questionnaire based on a modified version of the Hiroshima University Dental Behavior Inventory (HU-DBI) was administered to 250 dental students. Results: Significant differences (P<.05) were observed among students of different years in the degree of worrying about the color of the teeth, not having been to the dentist before and brushing each tooth carefully. Strongly significant differences (P<.001) were observed among students of different years in brushing the teeth twice daily, being satisfied with the appearance of the teeth, cleaning the teeth well without toothpaste, visiting dentist only when having a toothache, taking too much time to brush their teeth, worrying about having bad breath and using mouth rinse on a regular basis. Conclusions: Among dental students, the overall knowledge of oral health was good, even though there were deficits in knowledge in a few areas. The oral health attitudes and behavior of dental students improved with increasing levels of education. (Eur J Dent 2011;5:163-167)
Keywords: Oral health; Dental students; Questions; Oral attitudes; Oral health behavior